Clinical usefulness of a guideline‐based screening tool for the diagnosis of allergic rhinitis in asthmatics: The Self Assessment of Allergic Rhinitis and Asthma questionnaire. Issue 6 (25th July 2013) - Hojo, Masayuki; Ohta, Ken; Iikura, Motoyasu; Mizutani, Tomonori; Hirashima, Junko; Sugiyama, Haruhito
Abstract Background and objective Allergic rhinitis (AR) is common in asthmatic patients and may impair asthma control. However, this comorbidity is frequently missed. A simple test is needed to enable physicians to diagnose and evaluate the severity of both diseases. The Self Assessment of Allergic Rhinitis and Asthma (SACRA) questionnaire, which GINA and ARIA Japan committees developed in 2011, consist of questionnaires based on GINA and ARIA guidelines for the diagnosis and severity of AR and asthma, and a visual analogue scale (VAS) to evaluate the severity of both diseases. Our objective was to investigate the clinical usefulness of SACRA as a patient‐based screening tool for identifying asthmatic patients with AR. Methods SACRA, ACT (Asthma Control Test) and serum IgE RAST were performed in asthmatic patients. The correlation between SACRA and other parameters were analyzed. Results Four hundred twenty asthmatic patients were enrolled. Among 168 subjects who self‐reported no concomitant AR, 76 asthmatics scored one or more symptoms on SACRA. Eventually, 32 of these 76 subjects were diagnosed with AR by physicians based on laboratory data or physical examinations by ear, nose and throat specialists. The sensitivity and specificity of SACRA for the diagnosis of AR were 92% and 66%, respectively. The estimated prevalence of AR among asthmatics was 66%, almost identical to that of the previous nationwide study in Japan. The level of asthma control assessed by the VAS on SACRA and the ACT score showed a strong correlation (r = −0.700, P < 0.001). Conclusions SACRA may be a clinically useful tool for identifying bronchial asthma patients with AR.